The effect of an e-delivered dialogic reading programme, for middleclass caregiver-preschooler dyads, on the vocabulary and narrative skills of the pre-schoolers - Van der Hoven, Victoria (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.